1935
DOI: 10.1037/h0054248
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue, oscillation, and blocks.

Abstract: A study of the successive reaction times in the continuous performance of a homogeneous mental task discloses pauses or lengthened reaction times which appear at more or less regular intervals. In such simple tasks as color-naming, form-naming, code substitution, addition, naming opposites, and the like, these pauses occur on the average about three times a minute. In a previous article, (i), the author has described these pauses under the title 'blocks,' and has pointed out that they decrease in frequency and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1953
1953
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 1 publication
1
28
0
Order By: Relevance
“…A second possible source of interference on the pure lists derives from the work of Bills and Robinson (Bills, 1931(Bills, , 1935a(Bills, , 1935bRobinson and Bills, 1926), who suggested that homogeneous (pure) lists are more likely to suffer 'mental blocks.' They defined a mental block as a temporary stop in a continuous task and, using tasks such as continuously writing or saying 'ababab...' or 'abcdefabcdef...,' found that as task homogeneity and response competition increased, so did the tendency toward more frequent and longer mental blocks.…”
Section: Resultsmentioning
confidence: 99%
“…A second possible source of interference on the pure lists derives from the work of Bills and Robinson (Bills, 1931(Bills, , 1935a(Bills, , 1935bRobinson and Bills, 1926), who suggested that homogeneous (pure) lists are more likely to suffer 'mental blocks.' They defined a mental block as a temporary stop in a continuous task and, using tasks such as continuously writing or saying 'ababab...' or 'abcdefabcdef...,' found that as task homogeneity and response competition increased, so did the tendency toward more frequent and longer mental blocks.…”
Section: Resultsmentioning
confidence: 99%
“…This led to the formulation of the so-called Poisson-Erlang model. The notion of intermediate periods of distraction has already been suggested by many authors, such as Peak and Boring (1926), Bills (1931, 1935, and Berger (1982). The Poisson-Erlang model accounts for short-term variation in the latencies, but not for any long-term trend effect.…”
Section: The Inhibition Modelmentioning
confidence: 86%
“…This phenomenon appears to have been recognized first by Woodworth and Wells (232), and has subsequently been referred to as "fluctuations" or "oscillations" in behavior (Entwistle: 66; FlUgel: 74; and Philpott: 168). Bills (22,23,27) has made a thorough investigation of this effect during short-term fatigue and has referred to it as "blocking. "…”
Section: Response Blocking As An Indicator Of Fatiguementioning
confidence: 99%